2017
DOI: 10.1016/j.apmr.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Is Associated With Treatment Response From Nonpharmacologic Exercise Interventions in Knee Osteoarthritis

Abstract: Objective To examine the association between baseline mindfulness and response from exercise interventions in knee osteoarthritis (OA). Design Cohort Study; Responder analysis of a clinical trial subset Setting Urban tertiary care academic hospital Participants 86 participants with symptomatic, radiographic knee OA (mean age, 60 years; 74% female; 48% white) Interventions 12 weeks (twice per week) of Tai Chi or Physical Therapy exercise Main Outcome Measure(s) Treatment response was defined using Ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
(70 reference statements)
4
14
0
Order By: Relevance
“…For OA, a small pilot study showed a significant reduction of pain and improvement of function in patients who followed an 8-week meditation program. In OA patients, higher baseline "mindfulness" scores were also associated with a better response to exercise than patients with lower baseline mindfulness, suggesting again the synergistic effects of combining more disciplines within one intervention [27].…”
Section: Introductionmentioning
confidence: 97%
“…For OA, a small pilot study showed a significant reduction of pain and improvement of function in patients who followed an 8-week meditation program. In OA patients, higher baseline "mindfulness" scores were also associated with a better response to exercise than patients with lower baseline mindfulness, suggesting again the synergistic effects of combining more disciplines within one intervention [27].…”
Section: Introductionmentioning
confidence: 97%
“…A recent work observed that mindfulness exercises were significantly associated with a greater likelihood of response to non-pharmacological exercise interventions in knee OA [ 22 ]. In addition, the same group found a correlation between a predisposition to mindfulness and less pain and/or better quality of life in patients with knee OA [ 23 ]. Therefore, we conducted a randomized controlled trial (RCT) aiming to evaluate the efficacy on pain and function of a MBSR program, comparatively to its absence, in symptomatic knee and hip OA patients undergoing usual care during a 6-month follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a strong link between baseline mindfulness and the level of pain catastrophising has been verified in a previous study [ 61 ]. Lee et al’s study also confirmed this relationship in patients with knee osteoarthritis, which seems to suggest that higher mindfulness corresponds to a better response to TC training [ 67 ]. Up to now, limited study has investigated the longitudinal regression and correlation of mindfulness on the therapeutic effect of TC.…”
Section: Discussionmentioning
confidence: 74%